The connection between the university and the productive sector: technological transference (2012)
This paper analyzes the process of technological transfer from the university to the industry, firstly through a brief overview of the innovation role, and particularly of universities, according to various economic theories (Neoclassical Theory, Schumpeter and his followers, and Marxism) -- Next, the Bologna Process, a specific European case of technology transfer, is considered from empirical sources, official speeches, regulations and official documents -- Finally, the general trend of explicit relation in Argentina between the university and the productive sector is briefly analyzed from certain empirical evidence, official speeches and policies, in order to guide the understanding of this process in Latin America -- The main conclusion of the study aims to consider technological transfer as intrinsic and necessary for the contemporary capitalism